UMPAN BALIK GURU DAN TEMAN SEBAYA PADA KELAS MENULIS AKADEMIS: PANDANGAN SISWA UNTUK PENERAPAN YANG EFEKTIF - Ayudhia, Honesty Yonanda; Syafar, Dian Noviani (Universitas Putera Batam, 2025)
Students’ writing does not always show significant improvement despite receiving feedback from the teachers in writing class. Furthermore, some challenges faced by teachers and students in the feedback process include limited time for teacher reviewing and for students reviewing the feedback, and the curriculum constraints that must be followed. Most of the previous research focused on one type of feedback and study teacher and peer feedback separately. However, this study shifts the focus toward students’ insights and preferences on both types of feedback. Specifically, it explores three areas: students’ insights into teacher feedback and peer feedback, and how students integrate and prefer both types of feedback. The population consisted of 205 second-semester students in the English Education Program enrolled in 2024 who had taken a writing subject and had experienced both teacher and peer feedback in the writing process. As sample, 64 students met the research criteria and completed the questionnaire. Data were collected through close-ended questionnaire, developed from Nicol & MacFarlane-Dick (2006) seven principles of good feedback practice. The results were analyzed using percentage. It showed that the students saw the feedback from teacher and peers can complement each other in helping them improve their performance in writing class. They believed that the teacher’s feedback as detailed, clear, and reliable while peer feedback can support active learning, collaboration, and critical reflection. Although sometimes the students had conflicting feedback between teacher and peer, they could apply the most useful feedback in revising their work.